Unconscious Evidence. - Lyons, Jack (Philosophical Issues, 2016)
Can beliefs that are not consciously formulated serve as part of an agent's evidence for other beliefs? A common view says no, any belief that is psychologically immediate is also epistemically immediate. I argue that some unconscious beliefs can serve as evidence, but other unconscious beliefs cannot. Person-level beliefs can serve as evidence, but subpersonal beliefs cannot. I try to clarify the nature of the personal/subpersonal distinction and to show how my proposal illuminates various epistemological problems and provides a principled framework for solving other problems.